Facile preparation of N- and O-doped hollow carbon spheres derived from poly(o-phenylenediamine) for supercapacitors1. Issue 7 (21st February 2015) - Yuan, Chengqian; Liu, Xianhu; Jia, Meiye; Luo, Zhixun; Yao, Jiannian
<x xml:space="preserve">Abstract</x> Nitrogen and oxygen-doped hollow carbon spheres with enhanced electrochemical capacitance were prepared via pyrolysis of poly(o-phenylenediamine) hollow submicrospheres.